Radiographic pathology for technologists - Kowalczyk, Nina (Marylands Heights : Elsevier Mosby, 2014)
The 6th Edition of this text covers the injuries and abnormalities most frequently diagnosed using medical imaging to prepare you for what you are most likely to encounter on the job. It also features background discussions of key anatomy and physiology principles, along with imaging considerations for each disease categorized by type followed by a description of its radiographic appearance, signs and symptoms, and treatment.
Introduction to pathology -- Skeletal system -- Respiratory system -- Cardiovascular system -- Abdomen and gastrointestinal system -- Hepatobiliary system -- Urinary system -- Central nervous system -- Hemopoietic system -- Reproductive system -- Endocrine system -- Traumatic disease.
Includes bibliographical references and index.
Keywords: Diagnosis, Radioscopic; Diagnostic imaging; Pathology; Radiologic technologists; Radiography -- methods; Pathology -- methods